Transporting knowledge: a case study of meaning making on the pathways of science communication - Davis, Pryce (2018)
In this paper I study scientists, reporters, and news readers as they produce and/or interpret scientific texts. Imagining all of these actors as science learners allows me to compare across their individual understandings to follow ideas through the pathways of science communication. I provide a case study of how one scientist’s understandings causes difficulties for a reporter and two news readers. This case problematizes popular assumptions about the causes of public misunderstandings of science.